Measuring the Effect of Moral Leadership of Administrator toward Employees’ Morality in the Context of the Catholic School in the Ilocos Region, Philippines - Abun, Damianus; Margarita A. Galat; Theogenia Magallanes; Jecel M. Mansueto; Mary Joy Encarnacion (Technium Social Sciences Journal, 2021)
The study intended to determine the relationship between the moral leadership of administrators and the employees’ morality. To support the theory of the study, the literature was reviewed. The study used a descriptive correlational research design and it used descriptive and inferential statistics. Questionnaires were used to gather the data and it used weighted mean to determine the level of moral leadership of administrators and the morality of employees. Pearson r or Product Moment Correlation was used in determining the correlation between the moral leadership of administrators and the morality of employees. The study found that the morality of administrators was to a moderate extent and the morality of employees was high. Employees’ morality was higher than the administrators’. The study further found that there is a correlation between the moral leadership of administrators and the morality of employees. Therefore, the hypothesis is accepted.